Complete heart block in a patient with acute lymphoblastic leukaemia: teicoplanin as a possible cause and review of literature. (28th December 2012) - Sharif‐Yakan, A.; Arabi, M.; Musharrafieh, U. M.; Bitar, F. F.; Saab, R.; Abboud, M. R.; Muwakkit, S.
Summary What is known and Objective: Teicoplanin is a glycopeptide antibiotic used against documented or presumed methicillin‐resistant infections. We report a 31‐month‐old boy with acute lymphocytic leukaemia who developed permanent complete atrioventricular block (CAVB) necessitating pacemaker insertion after receiving teicoplanin for Staphylococcus epidermidis bacteremia. Case summary: Clinical assessment of the child revealed febrile neutropenia. After thorough assessment and work‐up, the patient was started on teicoplanin intravenously after which he had sudden onset of bradycardia. Electrocardiography showed CAVB that eventually required permanent pacemaker insertion. Twenty‐nine months from the incident, the patient is doing well. What is new and Conclusion: We report on a case of teicoplanin‐associated CAVB in a child with acute lymphoblastic leukaemia (ALL). This is one of only two similar cases reported in the literature. Teicoplanin remains the most probable cause. The use of teicoplanin should be approached cautiously in the setting of immunosuppression. Whether VZV contributed and teicoplanin triggered remains speculative. Physicians should be aware of this possible complication.